Early clinical efficacy of 3D-printed artificial vertebral body in spinal reconstruction after total en bloc spondylectomy for spinal tumors - Xiaodong Wang; Shaosong Sun; Yuanyuan Jiang; Bao Ren; Xiong Zhang; Jun Miao; Jingtao Ji; Ye Han (BMC Musculoskeletal Disorders)
Abstract Background Total en bloc spondylectomy (TES) is a recognized surgical approach for managing spinal tumors. With advancements in three-dimensional (3D) printing technology, the use of 3D-printed prosthetics for vertebral reconstruction post-tumor resection has gained traction. However, research on the clinical implications of these prosthetics remains limited. Methods This retrospective study evaluated patients who underwent TES for primary and metastatic thoracolumbar tumors at the Department of Spinal Surgery, Tianjin Hospital, between October 2017 and September 2020. These patients received anterior reconstruction with 3D-printed artificial vertebral bodies. Results 14 patients completed the surgery, with intraoperative blood loss ranging from 1,400 to 4,200 ml (mean 2,767 ± 790 ml) and operative duration between 240 and 520 min (mean 382 ± 75.9 min). The follow-up period extended from 7 to 43 months, with an average of 19.9 ± 9.5 months. Standardized prefabricated prosthetics were utilized in nine patients, while five received customized prosthetics. Throughout the follow-up, there were no reports of posterior connecting rod, 3D-printed prosthetic, or pedicle screw failures. Notably, one patient presented with significant prosthetic subsidence resulting in screw loosening, and three cases of prosthetic subsidence were observed. Conclusion The incorporation of 3D-printed prosthetics in TES procedures yielded favorable clinical outcomes. Further research is warranted to optimize these prosthetics for enhanced postoperative stability and patient-specific applications.